Analisis Faktor Yang Mempengaruhi Perilaku Konsumen Untuk Menggunakan Platform Crowdfunding Berbasis Zakat Untuk Menanggulangi Dampak Merugikan Covid-19 Pada UKM Kabupaten Nganjuk - Nurul Mutia Hidayah; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2022)
This study aims to determine the effect of performance expectations, business expectations, social influences, and condition of facilities on consumer behavior using the zakat-based Crowdfunding Platform to overcome the adverse impact of Covid-19 on SMEs in Nganjuk. This type of research is correlational research. The sample in this study was 52 respondents who were SMEs in Nganjuk Regency. The analytical method used is Multiple Linear Regression Analysis using SPSS 20. The results show that the independent variables, including performance expectations (X1), have a positive and significant effect on consumer behavior using the Zakat-based Crowdfunding Platform to overcome the adverse impact of Covid-19 (Y). Business expectations (X2) have a positive and significant effect on consumer behavior using the zakat-based Crowdfunding Platform to overcome the adverse impact of Covid-19 (Y). Social influence (X3) has a positive and significant effect on consumer behavior using the zakat-based Crowdfunding Platform to overcome the adverse impacts of Covid-19 (Y). The condition of the facility (X4) has a positive and significant effect on consumer behavior using the zakat-based Crowdfunding Platform to overcome the detrimental impact of Covid-19 (Y). At the same time, the variables of performance expectations, business expectations, social influences, and facility conditions have a simultaneous positive and significant effect on consumer behavior using the zakat-based Crowdfunding Platform to overcome the adverse impact of Covid-19